2017
DOI: 10.1016/j.biopsycho.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Fetal heart rate variability mediates prenatal depression effects on neonatal neurobehavioral maturity

Abstract: This study analyzed the mediating role of fetal heart rate variability (FHR) on prenatal depression and neonatal neurobehavioral maturity. A sample of 104 pregnant women was recruited and divided into two groups according to their Edinburgh Postnatal Depression Scale (EPDS) scores (depressed/non-depressed). FHR variability in response to speech stimuli was assessed at term (between 37 and 39 weeks gestation). The neonates were then assessed on the Neonatal Behavioral Assessment Scale (NBAS) during the first 5d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 52 publications
4
20
0
Order By: Relevance
“…Infants who were high on arousal showed a pattern of physiological instability, motor agitation, and irritability, which is consistent with research examining effects of prenatal depression on fetal and newborn neurobehavioral maturity (Figueiredo, Pinto, Pacheco, & Field, 2017;Van den Berg et al, 2005). For instance, Figueiredo et al found that fetuses whose mothers reported high depressive symptoms while pregnant had lower fetal heart rate variability.…”
Section: Discussionsupporting
confidence: 84%
“…Infants who were high on arousal showed a pattern of physiological instability, motor agitation, and irritability, which is consistent with research examining effects of prenatal depression on fetal and newborn neurobehavioral maturity (Figueiredo, Pinto, Pacheco, & Field, 2017;Van den Berg et al, 2005). For instance, Figueiredo et al found that fetuses whose mothers reported high depressive symptoms while pregnant had lower fetal heart rate variability.…”
Section: Discussionsupporting
confidence: 84%
“…According to the study conducted by Figueiredo et al on 104 pregnant women, thehe fetuses of non-depressed pregnant women showed higher HR variability than the fetuses of depressed pregnant women in response to speech stimuli, and later as neonates they performed more optimally on the Neonatal Behavioral Assessment Scale (on autonomic stability and total scores) [21]. In this study, the education of attachment skills reduced maternal anxiety and improved motor development in infants.…”
Section: Discussionsupporting
confidence: 46%
“…This result reinforced the major role of mother's prenatal depression symptoms on the emergence of further infant's sleep problems (Field et al., 2007; Gerardin et al., 2011; Nevarez et al., 2010). Also, this study adds to previous research on the adverse effects of mother's prenatal depression on infant development (e.g., Figueiredo, Pinto, Pacheco, & Field, 2017; Gentile, 2017; Stein et al., 2014), by reporting the adverse effects on infant's sleep problems. In their turn, infant's sleep problems may contribute to the emergence of mother's postpartum anxiety and depression symptoms (Ystrom, Nilsen, Hysing, Sivertsen, & Ystrom, 2017), which may help to explain the association between mother's prenatal and postpartum depression.…”
Section: Discussionmentioning
confidence: 74%